Question
upstudy study bank question image url

\begin{tabular}{l}9 Use the information given to find g . \\ In each case g is a linear function. \\ \( \mathrm{g}(x)=m x+c \), for some numbers \( m \) and \( c \). \\ \( \begin{array}{lll}\text { a } \mathrm{f}(x)=2 x+3 & \mathrm{fg}(x)=6 x+7 \\ \text { b } \mathrm{f}(x)=5-8 x & \mathrm{fg}(x)=21-4 x \\ \text { c } \mathrm{f}(x)=\frac{7-2 x}{5} & \mathrm{fg}(x)=\frac{15-6 x}{5} \\ \text { *d } \mathrm{f}(x)=6 x & (\mathrm{fg})^{-1}(x)=\frac{x+30}{18}\end{array} \) \\ \hline 0,1941\end{tabular}

Ask by Hills Logan. in the United Arab Emirates
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The linear functions \( \mathrm{g}(x) \) for each part are: - **a.** \( \mathrm{g}(x) = 3x + 2 \) - **b.** \( \mathrm{g}(x) = \frac{1}{2}x - 2 \) - **c.** \( \mathrm{g}(x) = 3x - 4 \) - **d.** \( \mathrm{g}(x) = 3x - 5 \)

Solution

Let's solve each part step-by-step to find the linear function \( \mathrm{g}(x) = m x + c \). ### **General Approach** Given: - \( \mathrm{f}(x) \) - \( \mathrm{fg}(x) = \mathrm{f}(g(x)) \) Since \( \mathrm{g}(x) = m x + c \), we substitute \( g(x) \) into \( f \): \[ \mathrm{f}(g(x)) = \mathrm{f}(m x + c) \] Set this equal to the given \( \mathrm{fg}(x) \) and solve for \( m \) and \( c \). --- ### **a.** **Given:** \[ \mathrm{f}(x) = 2x + 3 \\ \mathrm{fg}(x) = 6x + 7 \] **Solution:** \[ \mathrm{f}(g(x)) = 2(m x + c) + 3 = 2m x + 2c + 3 \] Set equal to \( \mathrm{fg}(x) \): \[ 2m x + 2c + 3 = 6x + 7 \] **Equate coefficients:** \[ 2m = 6 \implies m = 3 \\ 2c + 3 = 7 \implies 2c = 4 \implies c = 2 \] **Result:** \[ \mathrm{g}(x) = 3x + 2 \] --- ### **b.** **Given:** \[ \mathrm{f}(x) = 5 - 8x \\ \mathrm{fg}(x) = 21 - 4x \] **Solution:** \[ \mathrm{f}(g(x)) = 5 - 8(m x + c) = 5 - 8m x - 8c \] Set equal to \( \mathrm{fg}(x) \): \[ -8m x + (5 - 8c) = -4x + 21 \] **Equate coefficients:** \[ -8m = -4 \implies m = \frac{1}{2} \\ 5 - 8c = 21 \implies -8c = 16 \implies c = -2 \] **Result:** \[ \mathrm{g}(x) = \frac{1}{2}x - 2 \] --- ### **c.** **Given:** \[ \mathrm{f}(x) = \frac{7 - 2x}{5} \\ \mathrm{fg}(x) = \frac{15 - 6x}{5} \] **Solution:** \[ \mathrm{f}(g(x)) = \frac{7 - 2(m x + c)}{5} = \frac{7 - 2m x - 2c}{5} \] Set equal to \( \mathrm{fg}(x) \): \[ \frac{7 - 2m x - 2c}{5} = \frac{15 - 6x}{5} \] **Simplify and equate coefficients:** \[ -2m x + (7 - 2c) = -6x + 15 \] \[ -2m = -6 \implies m = 3 \\ 7 - 2c = 15 \implies -2c = 8 \implies c = -4 \] **Result:** \[ \mathrm{g}(x) = 3x - 4 \] --- ### **d.** **Given:** \[ \mathrm{f}(x) = 6x \\ (\mathrm{fg})^{-1}(x) = \frac{x + 30}{18} \] **Solution:** Let \( y = \mathrm{fg}(x) = \mathrm{f}(g(x)) = 6g(x) \). Given the inverse: \[ x = (\mathrm{fg})^{-1}(y) = \frac{y + 30}{18} \] Express \( y \) in terms of \( x \): \[ x = \frac{y + 30}{18} \implies y = 18x - 30 \] Since \( y = 6g(x) \): \[ 6g(x) = 18x - 30 \implies g(x) = \frac{18x - 30}{6} = 3x - 5 \] **Result:** \[ \mathrm{g}(x) = 3x - 5 \] --- ### **Final Answers:** - **a.** \( \mathrm{g}(x) = 3x + 2 \) - **b.** \( \mathrm{g}(x) = \frac{1}{2}x - 2 \) - **c.** \( \mathrm{g}(x) = 3x - 4 \) - **d.** \( \mathrm{g}(x) = 3x - 5 \)

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Bonus Knowledge

To find the linear function \( g(x) = mx + c \) in each case, we can utilize the relationship between functions \( f \) and \( g \), particularly focusing on their composition. For **a**: Given \( fg(x) = 6x + 7 \) and \( f(x) = 2x + 3 \), substitute \( g(x) \) into \( f \) and set it equal to \( fg(x) \). Thus, \( f(g(x)) = f(mx + c) = 2(mx + c) + 3 = 6x + 7 \). This gives us two equations: \( 2m = 6 \) (hence \( m = 3 \)) and \( 2c + 3 = 7 \) (thus \( c = 2 \)). So, \( g(x) = 3x + 2 \). For **d**: Here, we have \( f(x) = 6x \) and the inverse \( (fg)^{-1}(x) = \frac{x + 30}{18} \). From the composition \( fg(g^{-1}(x)) \), we want to find a \( g(x) \) such that \( f(g(x)) = x \). Assuming \( g(x) = mx + c \), we can find \( g \) by setting up the equations based on the inverse function format. After working through the composition, you’ll discover \( g(x) = \frac{x}{6} - 5 \). Now you've got all the pieces fitting together like a fun puzzle!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy